Laura Owens - Owens, Laura 1970- (Skira Rizzoli, 2015)
"This volume - modeled after the seminal book on Pablo Picasso's sketchbooks 'Je Suis Le Cahier: The Sketchbooks of Picasso' published in 1986 - brings together a range of critical and creative voices to consider her practice in depth."